THE ANALYSIS OF LOCAL TERMS ON SOCIAL MEDIA OF INDONESIAN TEENAGERS - Fachri Yunanda; Dinda Nuari; Kristina Angelika Br Panjaitan; Frederico Werend Renanta (UIBU, 2022)
A local term is a non-standard word that is used by groups of teenagers to communicate internally. This research attempts to provide relevant knowledge about local terms, specifically to identify the types and functions of the local terms, the influence of social media on Indonesian teenagers’ usage of local terms, also to analyze the impact of the local terms among teenagers. The researchers chose the descriptive qualitative method to explore the data and accomplish this study. The researchers used an online observation approach to obtain data. The data of this study were 50 samples of local terms from Facebook, Whatsapp, and Twitter. The slang theory from Allan & Burridge in (Savitri, 2021) is used to clarify the types of local terms in this research. The classification of local terms in this study is flippant, imitative, fresh and creative, clipping, and acronym.